If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 9) = 6(x + -3) + -9 Reorder the terms: 3(9 + x) = 6(x + -3) + -9 (9 * 3 + x * 3) = 6(x + -3) + -9 (27 + 3x) = 6(x + -3) + -9 Reorder the terms: 27 + 3x = 6(-3 + x) + -9 27 + 3x = (-3 * 6 + x * 6) + -9 27 + 3x = (-18 + 6x) + -9 Reorder the terms: 27 + 3x = -18 + -9 + 6x Combine like terms: -18 + -9 = -27 27 + 3x = -27 + 6x Solving 27 + 3x = -27 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 27 + 3x + -6x = -27 + 6x + -6x Combine like terms: 3x + -6x = -3x 27 + -3x = -27 + 6x + -6x Combine like terms: 6x + -6x = 0 27 + -3x = -27 + 0 27 + -3x = -27 Add '-27' to each side of the equation. 27 + -27 + -3x = -27 + -27 Combine like terms: 27 + -27 = 0 0 + -3x = -27 + -27 -3x = -27 + -27 Combine like terms: -27 + -27 = -54 -3x = -54 Divide each side by '-3'. x = 18 Simplifying x = 18
| q-1=-0.08 | | 6(x+1)=3(2x+4)-6 | | (2x+14)+(x+34)= | | 7(t-6)+8t=5(3t+4)-9 | | -6x+5+14x-4x= | | 0.05u+27.5=0.6u-11 | | (6x+4)+(7x-2)= | | 5-7=3x-5x | | -2(4s-6)-12=-3(4s+3)-3 | | 2(3h-2)=14 | | 2x-8x=-5 | | 2(x-3)=2x+4 | | -(w+5)=14 | | 9a^3+15a^2-36a=0 | | -3(5s-4)-12=2(9s+7)-2 | | 42x^2-15x-3=0 | | -2(-3x-w)-(2w-6x)= | | 5x^2+6x=12x-9 | | 8(x+2)=8x+16 | | 0.25x+.05(2-x)=.10(37) | | -5(x-4)=40 | | 8(x+6)-3(2x-7)=127 | | 1=d/10-12 | | 24v^2-9v+32v-12=0 | | 5y=-2.8 | | 7n-1=9+10n-12 | | 3x^2+2x-5=2x^2-2 | | 0.5=-8 | | 0.36(6)+0.04x=0.12(18+x) | | 4(6a-16)+2(2a+12)=4 | | 0.41x=8.2 | | -3(3y+v)+6(4v-4y)= |